Българското детско книгоиздаване през тоталитарния период [Bulgarian children`s publishing during the totalitarian period] - Kirilova, Katya (Годишник на Софийския университет „Св. Климент Охридски”, Факултет по журналистика и масова комуникация [Annual of Sofia University „St. Kliment Ohridski”, Faculty of Journalism and Mass Communication], 2015)
The subject of this study is an attempt to restore the model of the Bulgarian children`s book publishing during the totalitarian period. It focuses on the main changes which then occurred in children`s books by making a thorough research of the regulatory framework, the institutions,the professional attitude and the participants in children`s book publishing. The study gives an account of the leading children`s publishers, the achievements in illustrations, the top editions and book series. This commentary is made from a short time distance, but it is the starting point for further thorough research of the totalitarian period and Bulgarian children`s publishing.
https://katalog.adlr.link/Record/ai-53-596398